Real-Time Messenger RNA Dynamics in Bacillus subtilis - Sattler, Laura; Graumann, Peter L. (Frontiers in Microbiology, 2021)
Messenger RNA molecules have been localized to different positions in cells, and have been followed by time lapse microscopy. We have used MS2-mVenus labelled mRNA and single particle tracking to obtain information on the dynamics of single mRNA molecules in real time. Using single molecule tracking (SMT), we show that several mRNA molecules visualized via two MS2 binding sites and MS2-mVenus expressed in Bacillus subtilis cells show free diffusion through the entire cell, and constrained motion predominantly close to the cell membrane, and at the polar regions of the cells. Because constrained motion of mRNAs likely reflects molecules complexed with ribosomes, our data support the idea that translation occurs at sites surrounding the nucleoids. Squared displacement analyses show the existence of at least two distinct populations of molecules with different diffusion constants, or possibly of three populations, e.g. freely mobile mRNAs, mRNAs in transition complexes, or in complex with polysomes. Diffusion constants between differently sized mRNAs did not differ dramatically, and were much lower than that of cytosolic proteins. These data agree with the large size of mRNA molecules and suggest that within the viscous cytoplasm, size variations do not translate into mobility differences. However, at observed diffusion constants, mRNA molecules would be able to reach all positions within cells in a frame of seconds. We did not observe strong differences in the location of confined motion for mRNAs encoding mostly soluble or membrane proteins, indicating that there is no strong bias for localization of membrane protein-encoding transcripts for the cell membrane.